Testing the Dimensionality of Low Self-Control Across Three Groups of Chinese Adolescents - Ren, Ling (Journal of contemporary criminal justice, 2018)
The concept of Low Self-Control (LSC) has been a major focus of criminological theories since the publication of Gottfredson and Hirschi’s work in 1990. Although there is an increasing amount of literature devoted to exploring the precise theoretical construct of LSC, no consensus has been reached on the factorial structure of Grasmick et al.’s LSC measures. The purpose of this study is to investigate the factorial dimensionality of Grasmick et al.’s LSC measures in the Chinese setting. The data for this study come from three distinct samples collected in a Chinese province with a population of 47 million. The three samples represent high school students, troubled teens incarcerated in jail, and adjudicated juvenile offenders in prison in this province. Confirmatory factor analyses are utilized to conduct the factorial structure tests. Results provide strong support for a second-order or hierarchical model of LSC across the three groups. The key findings are discussed in terms of methodological, theoretical, and cultural dimensions.